PEREMPUAN SEBAGAI PEMIMPIN PADA RANAH PUBLIK (Dalam Tinjauan Metode Memahami Hadis Tekstual dan Kontekstual Syuhudi Ismail) - Fauzi, Ahmad Nur; Latifah, Siti Nurul Aini; Nasrulloh, Nasrulloh (EGALITA, 2023)
This paper examines the hadith about women being leaders and reviews the textual and contextual rules of Muhammad Shuhudi Ismail. This shows that hadith should not always be understood textually but by taking into account the socio-historical and contextual context of the hadith. The purpose of writing this article is to elaborate on the law of women's leadership in the public sphere. This research method uses a library research approach that aims to explore the study of women's leadership law in the public sphere. The analysis method in this study uses the content analysis method. The results of the research in this paper are: first, the textual hadith of the appointment of women to leadership was forbidden, and at that time women did not have any authority at all. Second, contextually, the understanding of the hadith of women becoming leaders changes with the passage of time, which is increasingly current. Third, classify women's hadith into leaders as hadith related to the situation that is happening (developing). Therefore, the hadith must be understood contextually because the content of the hadith instructions is temporal. The discussion about women's leadership has never subsided, so in the research, the author wants to contribute to complementing the study by trying to provide a different lens about women's leadership in the public sphere explored in the textual and contextual understanding of Syuhudi Ismail. This paper also contributes to strengthening the value of gender equality in Islamic religious teachings, thus encouraging the application of humanitarian principles and justice in society.